2020
DOI: 10.1017/cts.2020.5
|View full text |Cite
|
Sign up to set email alerts
|

Communication strategies for designing Facebook advertising campaigns to recruit rural participants to develop healthcare delivery interventions

Abstract: Background: Little is known about designing research recruitment campaigns that connect with underserved, geographically isolated rural populations. A theoretically informed process is needed to assist research teams and practitioners in their evaluation of Facebook’s feasibility as a recruitment tool and development of online materials for recruiting rural adults into healthcare delivery intervention development studies. Methods: We drew from research and theory in communication and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Develop social media recruitment templates for submitting IRB protocols and developing theoretically derived advertisements [ 8 ], and a risk matrix with examples of high and low-risk social media recruitment activities and the level of review required for each social media recruitment activity (task force and committee)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Develop social media recruitment templates for submitting IRB protocols and developing theoretically derived advertisements [ 8 ], and a risk matrix with examples of high and low-risk social media recruitment activities and the level of review required for each social media recruitment activity (task force and committee)…”
Section: Resultsmentioning
confidence: 99%
“…The full policies and procedures, including a risk matrix, is included in Multimedia Appendix 1 . Social media recruitment templates are included in Multimedia Appendix 2 and elsewhere [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have demonstrated interactivity in decision aids promote information sharing about clinical trials [ 12 ], whereas narrative interventions have been shown effective at conveying complex information through patient storytelling [ 13 ]. The use of cultural metaphors can effectively improve comprehension about randomization and intent to participate in a trial [ 14 , 15 ], while visual appeals that reflect social group memberships may increase perceptions of identity with the trial’s purpose [ 16 ]. Efforts to tailor recruitment materials for minorities have focused on framing participation as a way to reduce existing racial disparities in research, but have not yet been shown effective [ 17 ].…”
Section: Introductionmentioning
confidence: 99%